2007
DOI: 10.1093/molbev/msm063
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Population Structure in a Highly Social Top Predator, the Killer Whale

Abstract: Intraspecific resource partitioning and social affiliations both have the potential to structure populations, though it is rarely possible to directly assess the impact of these mechanisms on genetic diversity and population divergence. Here, we address this for killer whales (Orcinus orca), which specialize on prey species and hunting strategy and have long-term social affiliations involving both males and females. We used genetic markers to assess the structure and demographic history of regional populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
217
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(244 citation statements)
references
References 42 publications
(44 reference statements)
24
217
3
Order By: Relevance
“…Regarding sex‐biased dispersal, although mammals often exhibit a pattern of male‐biased dispersal and female philopatry (Greenwood, 1980) and sex‐biased dispersal is common in other cetacean species (e.g., Escorza Treviño & Dizon, 2000; Hoelzel et al., 2007; Krützen, Sherwin, Berggren, & Gales, 2004; Möller & Beheregaray, 2004), our results did not detect a bias in dispersal between the sexes (Figure 3). Although this result should be regarded with caution since the ability of the tests performed to detect the bias in dispersal is limited mainly due to the lack of extreme bias in dispersal, the low to moderate dispersal estimates, and the number of loci and samples analyzed (Goudet et al., 2002), previous franciscana dolphin studies also found a lack of sex‐biased dispersal (Costa Urrutia et al., 2012; Méndez et al., 2008), supporting our findings.…”
Section: Discussionsupporting
confidence: 41%
See 2 more Smart Citations
“…Regarding sex‐biased dispersal, although mammals often exhibit a pattern of male‐biased dispersal and female philopatry (Greenwood, 1980) and sex‐biased dispersal is common in other cetacean species (e.g., Escorza Treviño & Dizon, 2000; Hoelzel et al., 2007; Krützen, Sherwin, Berggren, & Gales, 2004; Möller & Beheregaray, 2004), our results did not detect a bias in dispersal between the sexes (Figure 3). Although this result should be regarded with caution since the ability of the tests performed to detect the bias in dispersal is limited mainly due to the lack of extreme bias in dispersal, the low to moderate dispersal estimates, and the number of loci and samples analyzed (Goudet et al., 2002), previous franciscana dolphin studies also found a lack of sex‐biased dispersal (Costa Urrutia et al., 2012; Méndez et al., 2008), supporting our findings.…”
Section: Discussionsupporting
confidence: 41%
“…In accordance with a previous mtDNA control region analysis (Gariboldi et al., 2015), high rates of gene flow (Table 3 and mtDNA results) and a lack of genetic differentiation between CL and NC were observed based on the microsatellite loci and mtDNA analyses (Table 2), suggesting that individuals from both localities form a panmictic population. This may be due to close geographic proximity between localities which may entail similar resource use, as it was previously suggested for this species (Costa Urrutia et al., 2012; Gariboldi et al., 2015; Méndez et al., 2008; Méndez, Rosenbaum, Subramaniam, et al., 2010) and other cetaceans (Fullard et al., 2000; Hoelzel et al., 2007; Natoli et al., 2005). In fact, individuals from NC and CL were found to fed primary on Loligo sanpaulensis (Paso Viola, 2014; Paso Viola et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In marine fishes, both niche partitioning and mate choice were affected by divergent selection on characters that resulted in sympatric speciation within the genus Hexagrammos (Crow et al, 2010). Among cetacean species, both killer whales (Orcinus orca) and bottlenose dolphins (Tursiops truncatus) show genetic differentiation among populations correlated to foraging specializations or habitat dependence (O. orca, Hoelzel et al, 2007;Moura et al, 2014;T. truncatus, Hoelzel et al, 1998;Natoli et al, 2005;Segura et al, 2006;CharltonRobb et al, 2011;Moura et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Foote and Morin (2015) suggest that the co-occurrence of populations in the same ocean doesn't necessarily imply that they differentiated in sympatry, which is clearly true. However, as Moura et al (2015) and others (for example, Hoelzel et al, 1998Hoelzel et al, , 2007 have discussed, it is the life history and behaviour of killer whales that suggest the potential for differentiation in sympatry. Although the proximity of resources brings killer whale pods into sympatry, the differential pattern of spatial and temporal habitat use, as well as fidelity to pods that forage by similar learned methods, could serve to isolate resource specialist communities reproductively.…”
mentioning
confidence: 99%